Agricultural Sciences: The Field for Promoting Human and Social Development - Paul, P.K.; Sinha, R.R.; Baby, Pappachan; Shivraj, K.S.; Saavedra, R.; Aremu, Bashiru (International Journal of Scientific Research in Biological Sciences, 2020)
Farming is a kind of process and methods of practicing cultivation with different kind of procedure; further agriculture is a broad concept than farming and cultivation. The scientific study, policies and procedure in respect of cultivation and further the agriculture is called Agricultural Science. It is worthy to note that, farming is done in a small area by the limited input but agriculture is consider and perform in a broader areas. Moreover in generally farming is considered as the way of cultivating for a family or small number of people whereas agricultural sciences is considered as just opposite of this. In the Agricultural there are lots of inputs and methods and thus it is known as Agricultural Systems. Further for dealing a broad area, scope and agenda with industrial support it is also refereeing as Industrial Agriculture. Modern agriculture systems are far different than traditional systems and it involves much wider in terms of production of food for humans as well as animal feeds. The worldwide increasing population has changed the way and methods of agricultural systems; today various new methods are directly adoptable in the agricultural systems. However in western world another name ?green revolution? has changed the systems of agricultural systems perfectly and as a result the farms are engaged in agriculture has engaged in more productively and types. Among the changes and new methods important are hydroponics, plant breeding, hybridization, gene manipulation, healthy soil management and nutrients, modern weeding controlling etc. Among the latest development and applications Genetic engineering is important which lead the capabilities beyond the traditional and higher yields and disease resistance. Modified seeds germinate faster, and thus grown rapidly. Genetic engineering of plants has proven controversial but still growing in many countries. The advancement of the technologies and management is also important and noticeable in agricultural sciences. The applications of the Information Technology and Management are important to note. This paper is conceptual in nature and deals with various aspects of agriculture specially the its basic, evolution, types, methods, emerging trends with reference to the sustainable agricultural development